KEPUTUSAN, PROPOSISI DAN PENALARAN DALAM LOGIKA YANG BERPERAAN TERHADAP MANAJEMAN DAKWAH - Subekti; Ninuk; Patnah Wati; Meity Suryandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Da'wah management refers to the process of organizing and managing da'wah activities to effectively and efficiently convey Islamic teachings to society. One significant approach in da'wah management is logic, which involves systematic and rational thinking in formulating strategies, decision-making, and evaluating da'wah programs. By applying logical reasoning, da'wah can be structured based on valid data analysis, strengthening arguments, and ensuring that the message delivered aligns with the characteristics and needs of the target audience. This article discusses how logic can assist in strategic planning for da'wah, making appropriate decisions, and improving the effectiveness of da'wah program evaluations. Through a logical approach, da'wah can be conducted in a more systematic and relevant manner within the context of a dynamic and diverse society. Keywords: Decision, Proposition, Reasoning, Da'wah Management